Pengaruh Bahan Pelleting terhadap Perkecambahan Benih Bawang Merah (Allium cepa L.) - Rajagukguk, Sion G.; Agustiansyah, Agustiansyah; Manik, Tumiar K.; Ginting, Yohannes Cahya (JURNAL AGROTROPIKA, 2023)
Shallot is an important commodity, but their productivity in Indonesia is still low. TSS can be used because of its higher production, longer shelf life, more resistance to disease pathogens, cheaper procurement and distribution costs, guaranteed seed quality, and high productivity potential, but has a small shape so it is difficult to plant so seed coating technology is needed. Seed pellets are coatings of seeds to change the shape, size and weight of seeds. This study aims to determine the effect of pelleting techniques on shallot seeds. This research was conducted with one treatment factor, namely without pelleting, soil + CMC, soil + CMC + Mycorrhizae, soil + CMC + Trichoderma, soil + CMC + Dolomite, soil + CMC + humic acid, soil + AG, soil + AG+ Mycorrhizae, soil +AG+Trichoderma, soil+AG+Dolomite, soil+AG+Humic acid. Each treatment was carried out with 3 replications so that 33 experimental units were obtained, with one experimental unit in the form of a planting media tray with 25 seeds each. The results of the study explained that the pelleting technique had no effect on germination, root length, coleoptile length, wet safe weight, dry safe weight, seed weight and had a significant effect on the emergence of plumules with the best treatment obtained in the soil. CMC + humic acid and seed pellet weight. stated that seed pellets can change the weight, size and shape of seeds so as to facilitate planting. The conclusion of this study is that shallot seed pelleting can be applied to shallot cultivation because it does not inhibit the growth and development of shallots and can facilitate the planting of shallot seeds. Key words:  Shallot, seed, pelleting, TSS